Expert model for the evaluation of potential competition performance in cross-country skiers exemplified by two evaluated athletes - Cernohorski, B.; Pustovrh, J. (Biology of Sport, 2008)
The objective of the present research was to obtain information on potential competition performance in cross-country skiers by the method of expert modelling. On the basis of expert knowledge, a model of potential performance (MFMPS) was constructed in the form of a decision tree, encompassing motor, functional, morphological, psychological, and sociological subspaces. For all base variables, normalisers were determined, and for all nodes in the MFMPS model, decision rules were determined according to the method applying dependent determination of weights. Potential competition performance of the sample of 14 subjects measured - cross-country skiers in the age of 17 and 18 years was assessed at all levels in the MFMPS model by means of the SMMS program. At the highest levels of the MFMPS model, the correlation between the scores of the variables and the criterion variable SLO_FIS was established by means of the Pearson correlation coefficient. The validity of the MFMPS model - by means of which 81% of the variance of the criterion variable was explained - was established. The model laid out in this way allows us to search for current weak and good points in the preparation status of an athlete, on which the direction and correction of the transformation process is based. In this way, objective longitudinal monitoring of the development of the athlete's potential is also ensured.